O6B.3 Risk of leukemia after chronic exposure to gamma radiation among ontario uranium miners?. (April 2019) - Do, Minh; Ramkissoon, Avinash; Berriault, Colin; Villeneuve, Paul; Demers, Paul
Abstract : Background and objectives: Increases in leukemia risk after exposure to gamma radiation have been well-demonstrated among nuclear energy workers and atomic bomb survivors. Although uranium miners are also exposed to gamma radiation, its health effects are not well characterized, and assumed to be insignificant relative to the effects of radon decay products. The objective of this study is to quantify the effects of whole-body gamma radiation exposure on the incident risk of leukemia among Ontario Uranium Miners. Methods: Based on a retrospective cohort of 28 546 uranium miners, leukemia cases were identified through record linkages with the Canadian Cancer Registry and Canadian Mortality Database. Gamma doses were estimated through dose prediction models and badge dosimeter readings collated by the National Dose Registry, blinded from case status. Person-years at risk of leukemia were stratified by exposure category, calendar period of employment, and attained age at risk. Poisson regression was used to model the risk (RR) of incident leukemia at increasing levels of cumulative gamma radiation exposure, adjusting for calendar period and attained age. Results: Between 1969 and 2005, 116 incident cases of leukemia were identified. On average, these miners were employed for 4.4 years with a mean cumulative dose of 5.25 millisieverts (mSv). With exposure lagged by 2 years, preliminary analyses showed that when compared to the referent group (0 mSv), those with >30 mSv of cumulative gamma dose had a non-statistically significant increase in the risk of leukemia diagnosis (RR=2.04, 95% CI: 0.93, 4.51) with increasing, linear trend (p=0.08). Conclusions: Although our results did not show a statistically significant relationship between gamma radiation and leukemia incidence, it is likely due to low statistically power. Future work may include pooling the Ontario Uranium Miners cohort with other similar cohorts to better quantify the potential associated risks.